Tetracarpidium conophorum seed extract improves markers of diabetic disease progression in streptozotocin-induced diabetic rats - Bamidele Stephen Ajilore, MBChB, PhD; Olubukola Sinbad Olorunnisola, PhD; Abiodun Olusoji Owoade, PhD (Elsevier, 2021)
Background: Tetracarpidium conophorum is one of the medicinal plants with probable efficacy for managing diabetes mellitus. Its leaf, root and seed have been recently reported to possess antihyperglycemic activity but its therapeutic benefit on diabetic disease progression is missing in literatures. This study aimed at investigating effects of Tetracarpidium conophorum seed (TECOSE) extract on biomarkers of therapeutic response in streptozotocin-induced diabetic rats. Methods: Powdered TECOSE was extracted with methanol using standard extraction procedure. Hyperglycemia was induced in rats with single intraperitoneal dose of 75 mg/kg/bwt streptozotocin. The rats were divided into five groups (n = 5): A- normal control, B- diabetic control, C, D and E were diabetic rats treated with TECOSE, metformin and insulin respectively for four weeks. Samples were collected for biochemical and hematological studies. Data obtained were analysed using One Way Analysis of Variance. Results: Percentage blood glucose reduction was 79, 79 and 73 in TECOSE, metformin and insulin groups respectively. HBA1c level was significantly (p<0.05) raised (14.89%) in diabetic-untreated rats when compared with normal control (2.84%), TECOSE (3.47%), metformin (5.68%) and insulin (6.36%) groups. TECOSE significantly (p<0.05) reduced levels of total cholesterol, low density lipoprotein cholesterol, haptoglobin, protein carbonyl content, lactate dehydrogenase and N-acetyl-glucosaminidase activities, platelet count, percentage lymphocyte, platelet/lymphocyte ratio, while it significantly (p<0.05) raised high density lipoprotein cholesterol, total leukocyte count, percentage neutrophil, and neutrophil/lymphocyte ratio when compared with untreated rats. Conclusion: The findings concluded that TECOSE improved biomarkers of therapeutic response and disease progression in diabetic rats.